Three different types of electric field disturbances affecting equatorial ionosphere during a long-duration prompt penetration event - Chakrabarty, D.; Rout, Diptiranjan; Sekar, R.; Narayanan, R.; Reeves, G.D.; Pant, Tarun K.; Veenadhari, B.; Shiokawa, K. (My University, 2015)
Coordinated digisonde and OI 630.0 nm airglow observations from Thumba (TVM), an Indian dip equatorial station, in conjunction with magnetic and geosynchronous particle flux measurements, reveal three different types of electric field disturbances in the equatorial ionosphere-thermosphere system (ITS) occurring in succession over a period of 6 h on a single night (22–23 January,2012; Ap = 24). These include (1) westward electric field perturbations owing to a pseudo-breakup and a substorm event, each lasting for about 30 min; (2) eastward electric field perturbations continuing for about an hour, owing to the southward excursion of Z component of interplanetary magnetic field (Bz); and (3) DP2-type fluctuating (period ∼40 min) electric field perturbation sustaining for about 4 h. The pseudo-breakup and the fully grown substorm events are found to be longitudinally localized and different in terms of response in the westward auroral electrojet index (AL) as well as geosynchronous electron/proton injections. The polarity of the prompt penetration of interplanetary electric field that affects the equatorial ionosphere is observed to be eastward during 2100–2200 IST (Indian Standard Time) which is observationally sparse but consistent with modeling studies. Interestingly, on the same night, DP2-type electric field fluctuations with ∼40 min periodicity and occasional eastward polarity (akin to daytime) are also found to affect the equatorial ITS for about 4 h (2200–0200 IST). The case study, thus, brings out different processes that constitute a long duration prompt penetration event which, otherwise, would have been categorized as a single event.
Keywords: Electric field; Equatorial ionosphere; Substorm; Airglow intensity